A EXTENSÃO UNIVERSITÁRIA ATRAVÉS DO PROJETO RONDON: PARTICIPAÇÃO DAS UNIVERSIDADES PÚBLICAS DE MATO GROSSO - Arno Rieder (Universidade Federal de Santa Catarina, 2012)
University extension is a purpose of universities. This practice has been brought about by various means and programs. In the late 1960s a model of extension was designed and entitled the Rondon Project. Nowadays the Project works on a second phase, one of recovery, after the first has been abolished in 1989. The opportunity provided by the Rondon Project for the exercise of university extension has been exciting and with positive impacts to the participants. The main purpose of this paper is to reveal impressions of participants and considerations on the involvement of two public universities in Mato Grosso in the two phases of the Rondon Project. The study is based on three references: bibliographical sources, (semi-open) interviews of participants, and the redeeming of experiences and impressions by a rondonist who took part in the Project on its first phase. It appears that the Federal University of Mato Grosso (UFMT) participated in operations of the Rondon Project in the first and second phases, while the University of Mato Grosso (UNEMAT) only in the latter, since it did not exist in the first phase. The rondonists believe that universities should intensify their involvement in these operations and that the importance of these proceedings is of immeasurable value for the purposes of university extension, leaving precious benefits not only for communities but also for academics and universities.